2020
DOI: 10.3390/jpm10040235
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Circulating Tumor Cells and Microsatellite Instability Status in Predicting Outcome of Advanced CRC Patients

Abstract: Colorectal cancer (CRC) remains one of the leading causes of cancer-related death due to its high metastatic potential. This study aimed to investigate the detection and heterogeneity of circulating tumor cells (CTCs) and the microsatellite instability (MSI) status in advanced CRC patients prior to any systemic front-line treatment. Peripheral whole blood was obtained from 198 patients. CTCs were detected using double immunofluorescence and a real time-polymerase chain reaction assay; whereas MSI status was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Zhang et al tested CTC in patients with bladder cancer planned for surgery and found that 44 cases (86.3%) were positive [35]. Many studies revealed that the detection of CTC in patients with colorectal cancer (CRC) [36], nonsmall cell lung cancer (NSCLC) [37], prostate cancer [38], and so on could predict the outcomes of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al tested CTC in patients with bladder cancer planned for surgery and found that 44 cases (86.3%) were positive [35]. Many studies revealed that the detection of CTC in patients with colorectal cancer (CRC) [36], nonsmall cell lung cancer (NSCLC) [37], prostate cancer [38], and so on could predict the outcomes of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 121 patients with advanced colorectal cancer, of whom 71 were CTC-positive, CTC positivity was predictive of the depth of invasion, lymphatic involvement, distant metastatic disease, TNM staging, and serum CEA level, and was overall predictive of less favorable PFS and OS, with persistent presence during chemotherapy also associated with poorer PFS and OS [104]. Additional studies have correlated baseline CTC count ≥3/7.5 mL with stage IV disease at diagnosis, at least three sites of metastasis, elevated CEA levels, and increased TNM staging [105,106]. Beyond disease characteristics, additional studies have supported the negative prognostication associated with CTC detection in both localized and advanced CRC prior to intervention [107][108][109][110].…”
Section: Colorectal Cancermentioning
confidence: 98%